2019
DOI: 10.3889/oamjms.2019.478
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Hyaluronic Acid Gel Injection in the Reconstruction of Interdental Papilla: A Randomized Clinical Trial

Abstract: BACKGROUND: Various techniques have been implemented to reconstruct the deficient interdental papilla.AIM: The present trial was conducted to assess the effect of injection of hyaluronic acid gel for the reconstruction of deficient interdental papilla.MATERIAL AND METHODS: Thirty-six deficient interdental papilla sites in ten patients were randomly allocated into two equal groups; intervention group who received the injection of hyaluronic acid (HA) gel and control group who received the injection of saline so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 10 publications
0
43
0
11
Order By: Relevance
“…Abdelraouf et al 2019, used 0.1 mm injectable Restylane (cross-linked HA 20mg/ml) for treatment of black triangles. The gain in height of the papilla in 6 months was 0.06 ± 0.17mm whereas the gain in surface area was found to be 11.8 ± 30.3. patients were significantly satisfied with the treatment results as well (26).…”
Section: Papilla Regenerationmentioning
confidence: 75%
“…Abdelraouf et al 2019, used 0.1 mm injectable Restylane (cross-linked HA 20mg/ml) for treatment of black triangles. The gain in height of the papilla in 6 months was 0.06 ± 0.17mm whereas the gain in surface area was found to be 11.8 ± 30.3. patients were significantly satisfied with the treatment results as well (26).…”
Section: Papilla Regenerationmentioning
confidence: 75%
“…Bertl et al 26 evaluated deficient papillae after filling with saline solution (10 papillae) and HA (11 papillae) and found no difference in papillary volume gain between the groups studied, in the period of 6 months. In contrast, Abdelraouf et al 25 studied a sample of 36 papillae and compared the same experimental groups during the same period of the study aforementioned, concluding that the deficient interdental papillae filled with HA showed better results than those filled with saline solution. The authors 25 believe that this difference in results occurred because the study by Bertl et al 26 uses different concentrations of HA and the papillary defects are in areas adjacent to implants, which alters the biological characteristics, whereas the papillary defects studied by Abdelraouf et al 25 are only around natural teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Another determining factor for the stability of long‐term results is the level of initial papillary deficiency associated with the degree of papillary reconstruction (complete or partial) 1,25 . Becker et al 11 showed no evidence of worsening of results in completely reconstructed papillae, for 25 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 43 IDP loss sites, 100% reconstruction was observed in 29 sites and 39-96% reconstruction was observed in 14 sites [8]. Sara et al reported that the HA filler could successfully reconstruct IDP and the reconstruction catered to patient satisfaction [9].…”
Section: Introductionmentioning
confidence: 99%